2D Electrocatalysts for Converting Earth‐Abundant Simple Molecules into Value‐Added Commodity Chemicals: Recent Progress and Perspectives. Issue 18 (1st October 2019) - Yin, Huajie; Dou, Yuhai; Chen, Shan; Zhu, Zhengju; Liu, Porun; Zhao, Huijun
Abstract: The electrocatalytic conversion of earth‐abundant simple molecules into value‐added commodity chemicals can transform current chemical production regimes with enormous socioeconomic and environmental benefits. For these applications, 2D electrocatalysts have emerged as a new class of high‐performance electrocatalyst with massive forward‐looking potential. Recent advances in 2D electrocatalysts are reviewed for emerging applications that utilize naturally existing H2 O, N2, O2, Cl − (seawater) and CH4 (natural gas) as reactants for nitrogen reduction (N2 → NH3 ), two‐electron oxygen reduction (O2 → H2 O2 ), chlorine evolution (Cl − → Cl2 ), and methane partial oxidation (CH4 → CH3 OH) reactions to generate NH3, H2 O2, Cl2, and CH3 OH. The unique 2D features and effective approaches that take advantage of such features to create high‐performance 2D electrocatalysts are articulated with emphasis. To benefit the readers and expedite future progress, the challenges facing the future development of 2D electrocatalysts for each of the above reactions and the related perspectives are provided. Abstract : Recent advances in 2D electrocatalysts are reviewed for emerging applications that utilize naturally existing nitrogen, oxygen, water, seawater, and methane as feedstocks. Areas of application considered include nitrogen reduction, two‐electron oxygen reduction, methane partial oxidation, and chorine evolution reactions to electrocatalytically generate ammonia, hydrogen peroxide, methanol, and chorine.